Performance analysis of PLA based hybrid filament composites reinforced with SPF/WTR for 3D printing - Norhazlin, Nur Batrisyia (2025)
Fused Deposition Modeling (FDM) is a widely used 3D printing method due to its cost efficiency and material flexibility. Presently, synthetic and carbon fibers are the predominant reinforcements. However, concerns regarding their environmental impact have prompted a shift towards more sustainable options. To address these issues, this research has proposed utilizing natural and recycled materials as a composites filler. Polylactic acid (PLA), a biopolymer derived from renewable sources like corn starch and sugarcane, accounts for over 60% of bio-based plastics globally. While PLA is biodegradable and offers environmental benefits, it has limited thermal and mechanical strength, restricting its broader use in functional applications. This study aims to enhance the performance of PLA by incorporating sugar palm fiber (SPF) that has high stiffness and renewability and waste tyre rubber (WTR) that offers superior impact resistance, flexibility, and energy absorption, which compensates for the brittleness of PLA and rigidity of SPF as reinforcements to develop hybrid composite filaments suitable for 3D printing. The primary objectives of this research include investigating the effects of filler loading on the mechanical and thermal properties of the composites. Three filler ratios (75% SPF: 25% WTR, 50% SPF: 50% WTR, and 25% SPF: 75% WTR) were evaluated. The second objective of this research was to examine the effect of infill density on the mechanical properties, morphology and surface quality which is three infill density (50%, 70% and 100%) were evaluated. The composites were analyzed for mechanical testing including tensile, flexural and impact, thermal analysis in Thermogravimetric analysis (TGA) and Differential scanning calorimetry (DSC), morphological analysis, and surface quality properties. For the first objective, the 75% SPF: 25% WTR composition showed the highest tensile 37.89 MPa and flexural strength 54.40 MPa, while the 25% SPF: 75% WTR combination recorded the greatest impact strength 4.30 kJj/m2. Thermal analysis on the TGA show that 75% SPF: 25% WTR has a great thermal stability while on the DSC show that 25%SPF:75%WTR has better heat resistance and dimentianal stability. For the second objective results on the mechanical testing, in terms of tensile strength, the 75% SPF: 25% WTR composite with a 50% infill densitydemonstrated superior strength compared to other configurations. For flexural strength, the 75% SPF: 25% WTR composite with a 100% infill density exhibited the highest performance, while the 25% SPF: 75% WTR composite with 100% infill density achieved the best impact resistance. Morphological analysis indicated that composites with higher SPF content and increased infill density exhibited more uniform internal structures. Increased infill density, particularly at 100% at 75% SPF: 25% WTR, contributed to smoother surface finish and enhanced load distribution, which correlated with improved tensile strength. These results indicate that SPF/WTR reinforced PLA composites could promote sustainable alternatives for material development in additive manufacturing.